2014
DOI: 10.1074/mcp.m114.041764
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Omic Analysis of Oropharyngeal Carcinomas Reveals Human Papillomavirus (HPV)–dependent Regulation of the Activator Protein 1 (AP-1) Pathway

Abstract: a HPV-positive oropharyngeal carcinoma (OPC) patients have superior outcomes relative to HPV-negative patients, but the underlying mechanisms remain poorly understood. We conducted a proteomic investigation of HPV-positive (n ‫؍‬ 27) and HPV-negative (n ‫؍‬ 26) formalinfixed paraffin-embedded OPC biopsies to acquire insights into the biological pathways that correlate with clinical behavior. Among the 2,633 proteins identified, 174 were differentially abundant. These were enriched for proteins related to cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 52 publications
6
20
0
Order By: Relevance
“…Nonetheless, consistent with gene expression studies, HPV-dependent upregulation of proteins involved in cell cycle, DNA replication processes, and downregulation of epidermal development/cell differentiation pathways was corroborated, and downregulation of keratinization and extracellular matrix proteins was newly observed (50)(51)(52) …”
Section: Proteomic Profilessupporting
confidence: 59%
See 1 more Smart Citation
“…Nonetheless, consistent with gene expression studies, HPV-dependent upregulation of proteins involved in cell cycle, DNA replication processes, and downregulation of epidermal development/cell differentiation pathways was corroborated, and downregulation of keratinization and extracellular matrix proteins was newly observed (50)(51)(52) …”
Section: Proteomic Profilessupporting
confidence: 59%
“…To address these issues, much work is underway to develop patient-derived xenograft models (58). Proteomics studies have been underrepresented in characterization of oropharyngeal cancer; however, as proteins represent cumulative effects of all upstream genomic aberrations and can provide indication of protein function, signaling, and cellular localization, their further application is warranted in the elucidation of clinical phenotypes (52). Finally, it is important to bear in mind that the molecular spectrum of HNSCC reflects strong influences by what appear to be significantly different tumor microenvironments in HPV þ versus HPV À tumors, which likely also play a critical role in therapeutic response, and undoubtedly require further interrogation.…”
Section: Summary and Future Perspectivementioning
confidence: 99%
“…Their tumors may share some biological features similar to the tobacco-driven HPV-unrelated tumors, which could also account for the nondifferential outcomes after salvage surgery by HPV status. 31,32 In addition, the nonsignificant difference in outcomes based on p16 status in our study may also be a function of the small sample size, and therefore limited study power to detect any potential difference. Fakhry et al 33 recently reported on disease progression of HPV-related and HPV-unrelated oropharyngeal SCC after definitive chemoradiation in the cohort of patients from the Radiation Therapy Oncology Group trials 0129 and 0522.…”
Section: Discussionmentioning
confidence: 81%
“…Thirteen of 19 patients (68%) with p16‐positive oropharyngeal SCC in the present study had more than 10 pack‐years of tobacco exposure. Their tumors may share some biological features similar to the tobacco‐driven HPV‐unrelated tumors, which could also account for the nondifferential outcomes after salvage surgery by HPV status . In addition, the nonsignificant difference in outcomes based on p16 status in our study may also be a function of the small sample size, and therefore limited study power to detect any potential difference.…”
Section: Discussionmentioning
confidence: 86%
“…It is possible that HPV-related carcinogenesis may occur in infected surface rather than reticulated epithelial cells, without a potential selective advantage from CK7 expression. This may explain the lack of any significant difference in previous proteome analysis of oropharyngeal SCC (45)(46)(47), and it may in future be worthwhile comparing protein expression between the oropharynx and other sites, especially given the known specificity of HPV to the oropharynx. It is also possible that non-HPV-related carcinogenesis may occur in CK7-expressing crypt epithelial cells (29), which could explain those cases with raised CK7 H-score, but HPV-and p16-negative oropharyngeal SCCs (24 cases).…”
Section: Discussionmentioning
confidence: 99%